Manajemen Stres pada Ibu Bekerja selama Pandemi Covid-19 di Desa Sidokumpul, Bungah, Kabupaten Gresik - Yurike Septianingrum; Lono Wijayanti; Erika Martining Wardani (Community Development Journal, 2021)
The dual role of being a mother and a worker gives stress to women who live it. The demand to work at home becomes a burden for them because they have to optimize their roles both as mothers and as workers, especially in conditions of imbalance in the work environment due to the current Covid-19 pandemic. The mother's inability to cope with the stressors received has the risk of causing depression in the mother. This community service aims to increase the knowledge of mothers about stress management in working mothers during the Covid-19 pandemic. The activities are carried out within 1 month. The method used is education and demonstration of positive thinking virtually via YouTube. This community service activity was attended by 17 mothers. Mother's knowledge was measured using a questionnaire via a google form. The results of community service show that there is an increase in knowledge of mothers after being given virtual counselling